Wound healing of experimental equine skin wounds and concurrent microbiota in wound dressings following topical propylene glycol gel treatment - Labens, Raphael; Raidal, Sharanne; Borgen-Nielsen, Cathrine; Pyecroft, Stephen; Pant, Sameer D.; De Ridder, Thomas (Frontiers in Veterinary Science, 2023)
Introduction Topical wound treatments rely on carrier formulations with little to no biological impact. The potential for a common vehicle, a propylene glycol (PG) gel, to affect wound healing measures including microbiota is not known. Microbiome characterization, based on next generation sequencing methods is typically performed on tissue or directly obtained wound fluid samples. The utility for primary wound dressings to characterize equine wound microbiota in the context of topical treatments is currently unknown. This investigation reports the topical effect of an 80% PG based gel on wound healing and microbiota in wound dressings. Methods Experiments were performed in six mature horses utilizing a surgical, distal limb wound model, histology of sequential wound biopsies, photographic wound measurements and microbiota profiling via 16s rRNA sequencing of wound dressing samples. Experimental wounds were surveyed for 42 days and either treated (Day 7, 14, 21 and 28; at 0.03 ml/cm2) or unexposed to the PG gel. Wound surface area, relative and absolute microbial abundances, diversity indices and histologic parameters were analyzed in the context of the experimental group (treatment; control) using qualitative or quantitative methods depending on data characteristics. Results Compared to controls, treatment slowed the wound healing rate (17.17 ± 4.27 vs. 18.56 ± 6.3 mm2/day), delayed the temporal decline of polymorphonucleated cells in wound beds and operational taxonomic units (OTU) in wound dressings and lowered alpha-diversity indices for microbiota in primary wound dressing. Relative abundances of OTUs were in line with those previously reported for equine wounds. Clinical outcomes 42 days post wounding were considered similar irrespective of PG gel exposure. Discussion Results highlight the potential for vehicle exposure to alter relevant wound outcome measures, imposing the need for stringent experimental control measures. Primary wound dressings may represent an alternate sample source for characterization of the wound microbiome alleviating the need for additional interventions. Further studies are warranted to contrast the microbiome in wound dressings against that present on wound surfaces to conclude on the validity of this approach.